Исследование процесса вибрации механической системы методами ячеек и фундаментальных контуров - Лелюк, Николай Анатольевич (НТУ "ХПИ", 2008)
Рассмотрены два метода формирования уравнений состояния для исследования вибрации механической системы. На примере одной механической системы доказана идентичность этих методов. Приведены правила формирования уравнений модели механической системы на основе метода ячеек.

Two methods used for forming of state equations at researching vibration processes in a mechanical system are considered. On a base of a particular mechanical system the identity of these methods is proved. The rules of these equations forming are resulted for the cells method.
Research of vibration process in a mechanical system by methods of cells and fundamental contours
Keywords: электрические аппараты; метод хорд; моделирование; граф механической системы; модифицированный граф; матрица фундаментальных контуров; mechanical system; vibration process; method of cells; method of fundamental contours